2017
DOI: 10.1080/08941939.2016.1269854
|View full text |Cite
|
Sign up to set email alerts
|

Current Molecular and Genetic Aspects of Pancreatic Cancer, the Role of Metastasis Associated Proteins (MTA): A Review

Abstract: Carcinogenesis and implicated oncogenes, either activators or repressors, concentrate much research interest, as well as being useful as biomarkers and for targeted therapy. MTA proteins could become useful diagnostic and prognostic biomarkers in current management of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 117 publications
0
7
1
Order By: Relevance
“…These results suggest that these peptides could have broader applicability. Several authors have reported that MTA1 is expressed at low levels in most normal cells [7, 10, 15], and accordingly, we did not detect significant lysis activity by peptide-induced CTLs toward the normal cells HUVEC and Het-1A, perhaps because of the weak MTA1 expression in these cells. Although MTA1-specific T cells can lyse MTA1 + tumor cells rather than normal cells, which express low levels of MTA1, and the body weight of mice in the peptide or protein group was not affected.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…These results suggest that these peptides could have broader applicability. Several authors have reported that MTA1 is expressed at low levels in most normal cells [7, 10, 15], and accordingly, we did not detect significant lysis activity by peptide-induced CTLs toward the normal cells HUVEC and Het-1A, perhaps because of the weak MTA1 expression in these cells. Although MTA1-specific T cells can lyse MTA1 + tumor cells rather than normal cells, which express low levels of MTA1, and the body weight of mice in the peptide or protein group was not affected.…”
Section: Discussioncontrasting
confidence: 57%
“…Our previous study found that MTA1 was upregulated in tumor cells treated with chemotherapy drugs such as cisplatin, 5-fluorouracil, and pacitaxel. Therefore, MTA1 has been considered an ideal target for cancer immunotherapy [15]. However, the immune-dominant CTL epitopes of MTA1 have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the upregulation of MTA2 in many types of cancers, such as gastric cancer 14, 15, breast cancer 11, and non-small-cell lung carcinoma (NSCLC) 16. MTA2 was observed to be highly expressed in pancreatic ductal adenocarcinoma (PDAC) and correlated with aggressive properties and poor prognosis 17.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that there are significant differences between Asian and Caucasian populations in genetic and epigenetic background, dietary, environmental factors (114, 115). These factors are essential for not only initiation and progression, but also metastasis of cancers (116, 117). Mutations and extensive polymorphisms of SIRT1 were found in Chinese and Japanese (118121) and 41 cancer lines (122).…”
Section: Discussionmentioning
confidence: 99%